Erythrasma: Pathogenesis and Diagnostic Challenges - Martínez Ortega, Jesús Iván; Franco González, Samantha (2024)
Erythrasma is a common chronic superficial bacterial infection caused by Corynebacterium minutissimum, a lipophilic, diphtheroid, filamentous, gram-positive bacillus and normal inhabitant of the skin flora. Commonly found in intertriginous spaces, this bacterium releases a porphyrin that causes lesions to fluoresce under a Wood’s lamp, aiding diagnosis. Despite its clinical relevance, the pathogenesis remains understudied. We present a case of a 43-year-old woman with a history of hypertension, type 2 diabetes mellitus, and obesity who exhibited an erythematous eczematous plaque with characteristic coral-red fluorescence under Wood’s lamp. The diagnosis was confirmed through negative skin scrapings for candidiasis and dermatophytosis. A two-week course of topical clindamycin resulted in complete resolution. Given the condition’s frequent coexistence with other pathologies, accurate diagnosis and effective treatment are essential. Topical treatments are usually more convenient. The hypothesis that hydrophobic and lipophilic interactions in intertriginous areas contribute to the pathogenesis of erythrasma requires further experimental validation.